Uppvisande av agitativt beteende hos hund under buprenorfinpåverkan - Mannsikka, Lisa (2009)
The intention of this study is to investigate possible excitation on dogs due to buprenorphine treatment. The reason for it to be about buprenorphine and not any other opioid is due to its relevance being one of the most popular opioids in animal care, as well as the authors own experience with what seems to be buprenorphine induced excitation in her own dog. The study consists of a literature review and an internet based survey containing thirty questions sent out to twelve animal clinics and animal hospitals. Significant agitative effects on behavior has been found in studies on horses, sheep, goats, rats and mice, but no one shows the effects of buprenorphine on dogs. The literature on opiod effects on dog behavior seems sparse. According to one study dogs, together with humans and rhesus monkeys, belongs to the grouping of animals that tend to react rather with sedation than excitation in contrast with horses, cats, rats and mice that are more sensitive to opioid induced excitatory side effects. However, there are studies documenting agitative behaviors in dogs induced by other opioids than buprenorphine. One author describes increased vocalization and restlessness in dogs affected by butorfanol, further sufentanil caused sensitivity to sounds and excitation in a study on beagels. In the internet survey, it was revealed that more than 70% of the respondees had the opinion that continuous vocalization and excitation could be dangerous to the patient. Work experience had a very large influence on whether the respondees reported that it was hard to see the difference of pain behavior and stressed behavior with other causes. This is of interest considering that 55 % of the respondees reported 10 years or less of work experience. There is no unambiguous support for the notion that a significant proportion of dogs would react excitatory on analgetics using buprenorphin, but there is not enough literature speaking against it either. Thus more research in the subject is recommended.